Satisfaction With Health Care Among Patients Navigated for Preventive Cancer Screening. (September 2018) - Hermann, Emilia A; Ashburner, Jeffrey M; Atlas, Steven J; Chang, Yuchiao; Percac-Lima, Sanja
Background: Patient navigation (PN) programs can improve cancer screening in underserved populations. PN may advance quality and equity of care by supporting individuals at increased risk of not receiving recommended care. Objective: To evaluate patient satisfaction with medical care and PN for cancer screening. Methods: We conducted a telephone survey of patients enrolled in a randomized control trial evaluating the impact of PN for cancer screening to assess their satisfaction with overall medical care and the PN program. We measured patient satisfaction with medical care using the Patient Satisfaction Questionnaire-18 and evaluated patient satisfaction with PN in the navigated group using the Patient Satisfaction with Interpersonal Relationships with Navigator questionnaire. Key Results: Satisfaction surveys were completed by 114 navigated and 108 non-navigated patients (33% response rate). Patients who received PN had higher satisfaction scores with overall medical care (71.0 vs 66.8; P < .001). Conclusions: Our findings show that patients at high risk of nonadherence with comprehensive cancer screening were satisfied with PN and suggest that PN could positively influence patient satisfaction with overall medical care.